Peningkatan Literasi Hak Keperdataan Tersangka dan Terdakwa Melali Penyuluhan Hukum bagi Warga Binaan Rutan Kelas I Depok - Wardani Rizkianti; Dwi Desi Yayi Tarina; Dwi Aryanti Ramadhani; Sulastri; Aisyah Nikita Permata Putri (PT. Adriani Mandiri Publisher, 2026)
The status of being a suspect or defendant is often misunderstood as the loss of all legal rights, including civil rights that remain inherent in every individual as a subject of civil law. This misconception contradicts the principle of the presumption of innocence and may potentially harm family members and other parties who have legal relationships with the suspect or defendant. This community service activity aimed to improve the legal literacy of inmates at Class I Depok State Detention Center (Rutan I Depok) regarding civil rights that remain applicable throughout the criminal justice process, in accordance with the new paradigm introduced by Law Number 1 of 2023 concerning the Criminal Code (KUHP) and Law Number 20 of 2025 concerning the Criminal Procedure Code (KUHAP). The activity was conducted on June 24, 2026, involving 36 inmates, using an educational lecture method combined with case studies and question-and-answer discussion sessions. The materials covered asset ownership rights, family relationships and child custody rights, civil legal actions during detention, protection of employment relationships, as well as legal protection mechanisms through pretrial proceedings and civil lawsuits. The results demonstrated an increase in participants’ awareness regarding the continuity of civil rights and the importance of legally protecting civil interests. Therefore, this activity is relevant as an initial step toward strengthening civil rights protection for vulnerable groups within detention environments.